Ameloblastic fibrodentinoma involving anterior maxilla: A rare case report - Shailaja Sankireddy; Atul Kaushik; Bhargavi A Krishna; Asha Latha G Reddy; V C Vinod; V Sridevi (Wolters Kluwer Medknow Publications, 2013)
Ameloblastic fibroma (AF) and related lesions comprise a complex group of mixed odontogenic tumors. Ameloblastic fibrodentinoma (AFD) is a rare tumor and is considered as a histological variant of AF showing inductive changes that lead to the formation of dentin. Although the most common site for this tumor is the posterior mandible, hereby we are reporting a case of AFD in the anterior maxillary region which is a very rare site for this group of tumors. The present case report highlights the clinical, radiological and histological presentation of AFD in order to raise awareness for the earlier diagnosis and precise management of this rare pathological entity.